2020
DOI: 10.1016/s0959-8049(20)30812-1
|View full text |Cite
|
Sign up to set email alerts
|

Real world evidence of palbociclib use in metastatic hormone positive HER negative metastatic breast cancer in Indian population

Abstract: Data analysed included demographics, disease characteristics, treatments, toxicities, response rates and survival outcomes. Inferential statistical analysis was completed using frequency table calculations, Cox proportional hazard model for univariate analysis and Kaplan Meier curves for survival data and time to event data. 3. We identified 271 pts, median age was 60 years (31-88) and divided them into 2 patient cohorts. 38% of pts (n = 103) were ≥65 years (Group 1) with a median age of 72 years (65-88) and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Febrile neutropenia requiring antibiotics developed in a small minority of patients (9%) attesting to the safety of these drugs in routine outpatient clinical practice. Toxicity or intolerance requiring treatment discontinuation was seen in a small proportion of patients in our study (3.0%), comparable to that seen in PALOMA-3 (4%) [4] & MONALEESA-7 (4%), studies [7], and that reported in real-world setting from India (2.7%) [16].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Febrile neutropenia requiring antibiotics developed in a small minority of patients (9%) attesting to the safety of these drugs in routine outpatient clinical practice. Toxicity or intolerance requiring treatment discontinuation was seen in a small proportion of patients in our study (3.0%), comparable to that seen in PALOMA-3 (4%) [4] & MONALEESA-7 (4%), studies [7], and that reported in real-world setting from India (2.7%) [16].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, appraisal of new treatments in routine practice is an important component of the evidence base. Although a few studies have analyzed the real-world outcomes with CDK 4/6 inhibitors [11][12][13][14] such data from India is scant [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[5] The PFS and toxicity analysis results are consistent with other reports of routine clinical practice, that is, real-world evidence from India and other countries and the global clinical trials. [6][7][8][9][10][11][12][13][14][15][16][17] The observed OS is lower than reported in real-world studies and clinical trials. Our analysis suggests that patients who were less heavily pre-treated had better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of palbociclib was consistent with that seen in clinical practice and trials in India and other countries. [6,[10][11][12]15,16] The major limitation of our study is its retrospective nature as that introduces a potential bias in patient selection, also it being a single-institutional single-arm study with a small sample size.…”
Section: Discussionmentioning
confidence: 99%